2018
DOI: 10.1073/pnas.1716855115
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR/Cas9 cleavages in budding yeast reveal templated insertions and strand-specific insertion/deletion profiles

Abstract: Harnessing CRISPR-Cas9 technology provides an unprecedented ability to modify genomic loci via DNA double-strand break (DSB) induction and repair. We analyzed nonhomologous end-joining (NHEJ) repair induced by Cas9 in budding yeast and found that the orientation of binding of Cas9 and its guide RNA (gRNA) profoundly influences the pattern of insertion/deletions (indels) at the site of cleavage. A common indel created by Cas9 is a 1-bp (+1) insertion that appears to result from Cas9 creating a 1-nt 5' overhang … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
123
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 51 publications
17
123
1
Order By: Relevance
“… Cas9-nuclease mechanism : consistent with previous reports ( 59 ), our findings suggest that Cas9 nuclease activity followed by NHEJ is the mechanism underlying the duplication of nucleotides at repaired sites (Figure 5A ). This finding is also supported by a recent study in budding yeast ( 67 ) and a biochemical analysis of Cas9 nuclease activity ( 68 ). Interestingly, the latter study also showed that the Cas9 RuvC domain is capable of exonuclease activity on the cleaved target which can lead to its bidirectional degradation ( 68 ).…”
Section: Discussionsupporting
confidence: 81%
“… Cas9-nuclease mechanism : consistent with previous reports ( 59 ), our findings suggest that Cas9 nuclease activity followed by NHEJ is the mechanism underlying the duplication of nucleotides at repaired sites (Figure 5A ). This finding is also supported by a recent study in budding yeast ( 67 ) and a biochemical analysis of Cas9 nuclease activity ( 68 ). Interestingly, the latter study also showed that the Cas9 RuvC domain is capable of exonuclease activity on the cleaved target which can lead to its bidirectional degradation ( 68 ).…”
Section: Discussionsupporting
confidence: 81%
“…These indels, usually smaller than 50 bp, can be predicted from DNA sequence with high precision (5)(6)(7)(8). In particular, frequent occurrence of 1 bp insertions templated from around the cut site has been linked to Cas9-induced DSBs with 1 nt 5' overhang (9,10). The size of indels is typically increased by NHEJ inhibition, while inhibition of the core MMEJ proteins, such as Parp1 and Polθ, decreases them (3,(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the protocol allows for better control of the cutting step, so that it can also be used, for example, to examine repair of DSBs in the same fashion that it is done in S. cerevisiae (Lemos et al, 2018). In this work, we have used the system to confirm that faithful NHEJ is a major repair mechanism of chromosomal DSBs in C. glabrata.…”
Section: Discussionmentioning
confidence: 99%
“…In yeasts, the system has been used, first and foremost, in S. cerevisiae, for genome engineering (DiCarlo et al, 2013) but also for the study of the repair of DSBs (Lemos et al, 2018) and for mating-type switching (Xie et al, 2018). Several versions of the CRISPR-Cas9 systems have also been designed for C. glabrata (Cen, Timmermans, Souffriau, Thevelein, & Van Dijck, 2017;Enkler, Richer, Marchand, Ferrandon, & Jossinet, 2016;Vyas et al, 2018), with success in obtaining repair events of both NHEJ and HR types.…”
mentioning
confidence: 99%